Poverty in Ecuador - Sanchez-Paramo, Carolina (World Bank, Washington, DC, 2012)
The note looks at poverty in Ecuador, assessing macroeconomic developments through its policies to maintain stability with fiscal discipline, and increase economic productivity and competitiveness, in particular, the 1998/99 crisis, the 2000 dollarization and their effect on poverty. From 1990 to 2001, national consumption-based poverty rose from 40 to 45 percent, and the number of poor people increased from 3.5 to 5.2 million. Poverty increased by over 80 percent in urban areas at the Costa and the Sierra, was stable in the rural Costa, and rose 15 percent in the rural Sierra. Poverty rates continued to be highest in rural areas, but rapid urbanization increased the number of poor people living in urban areas. Employment is the main income source, frequently the only one, for most urban families. Thus policies that generate employment and wage income are crucial for reducing urban poverty. The 1998/99 crisis sent employment and real labor income plummeting, urban poverty rose, and poor urban households resorted to various coping strategies, such as increased labor force participation, and migration. Poverty declined slowly after 2000, reflecting just a weak formal employment creation. It is stipulated social expenditures could be used more effectively, for significant improvements are needed in education provision, and quality, especially in rural areas, while health service coverage must be expanded and integrated better across different subsystems, and providers.